2017
DOI: 10.1038/cddis.2017.211
|View full text |Cite
|
Sign up to set email alerts
|

MiR-125b regulates proliferation and apoptosis of nasopharyngeal carcinoma by targeting A20/NF-κB signaling pathway

Abstract: MiR-125b is aberrantly expressed and has a role in the various types of tumors. However, the role and mechanism of miR-125b in nasopharyngeal carcinoma (NPC) are unclear. In this study, we investigated the role and mechanism of miR-125b in NPC. We observed that miR-125b was significantly upregulated in the NPC tissues relative to normal nasopharyngeal mucosa (NNM), and its increment was correlated with poor patient survival, and was an independent predictor for reduced patient survival; miR-125b promoted NPC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 48 publications
2
66
0
Order By: Relevance
“…10,12 The dysregulated miRNAs play an important role in NPC tumorigenesis and progression by promoting NPC cell proliferation, invasion, and angiogenesis. [13][14][15][16] It has been found that miR-125b is upregulated in NPC, and it can promote NPC cell proliferation and inhibit cell apoptosis by targeting A20 and activating the NF-kB signaling pathway. 13 miR-506 can inhibit NPC tumor growth and metastasis through inactivating the Wnt/β-catenin signaling pathway by targeting LHX2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,12 The dysregulated miRNAs play an important role in NPC tumorigenesis and progression by promoting NPC cell proliferation, invasion, and angiogenesis. [13][14][15][16] It has been found that miR-125b is upregulated in NPC, and it can promote NPC cell proliferation and inhibit cell apoptosis by targeting A20 and activating the NF-kB signaling pathway. 13 miR-506 can inhibit NPC tumor growth and metastasis through inactivating the Wnt/β-catenin signaling pathway by targeting LHX2.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] It has been also found that miRNA expression is dysregulated in NPC, [10][11][12] and the dysregulated miRNAs can promote NPC cell proliferation, invasion, and angiogenesis, including miR-125b, miR-506, miR-142-3p, miR-23a, and so on. [13][14][15][16] Thus, previous studies indicate that miRNA plays vital roles in NPC carcinogenesis and development. It also should be noted that further exploration of the function and mechanism of miRNA involved in NPC development and progression would provide novel therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that miR‐125b plays a crucial role in cell growth, apoptosis, and metastasis. In nasopharyngeal carcinoma, miR‐125b promoted cancer cell proliferation and apoptosis inhibition by targeting A20, a negative regulator of NF‐κB signaling pathway (Zheng et al., ). In colorectal cancer, the high expression of miR‐125b inhibited proliferation but promoted metastasis by direct targeting to myeloid cell leukemia 1 (MCL1), a Bcl2 family member (Zhang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the p53 gene occur in nearly 50% of human malignancies, which greatly increases the cell resistance to radiation [27,28]. Studies have shown that up-regulation of Bcl-2 expression can inhibit the expression of Bax, caspase-3 and other apoptotic genes and promotes the survival of nasopharyngeal carcinoma cells, thus playing a role in the development and metastasis of nasopharyngeal carcinoma [29]. Fas belongs to the TNF receptor family.…”
Section: Mechanism Of Radiotherapy Resistance In Nasopharyngeal Carcimentioning
confidence: 99%